Translation Techniques Used by English as a Foreign Language Students in Translating English Text - Nafisah, Bq Zuhrotun; Setianingsih, Tri (Humanitatis : Journal of Language and Literature, 2025)
Due to the disparities between the source and target languages, some techniques are used during the translation process to ensure that the translated works are equivalent. The study aims to analyze the translation techniques suggested by Molina and Albir used by the fifth-semester English as a Foreign Language students of the English Department of Mandalika University of Education in translating English text into Indonesian text. It also implies that the students have problems with translation. This was descriptive qualitative research. The data are collected through a test by giving them an English text taken from Kompas magazine to be translated into an Indonesian text. And through a structured interview to investigate the problems they faced in translating. After collecting the data, it was analyzed using Miles and Huberman’s interactive data analysis model. The findings indicate that there are six translation techniques. Among them, borrowing is dominantly used as a technique in translating the SL, with the highest use being 77 of 118 sentences that applied the technique. The interview results revealed that their main challenge in translating is preserving the intended meaning while adjusting for contextual and cultural variations and the lack of adequate knowledge about it.